Fluctuation behavior of the degree growth dynamics in complex networks - Chang, Hanyun; Qian, Jiang-Hai (AI Society & STMIK Indonesia, 2024)
The standard network theory predicts the ﬂuctuation of the degree growth rate is interval-independent, whereas the evidence witnessed in Internet shows an inconsistent result, which raises the concern of many existing relevant studies that apply just single observation interval. To check whether such inconsistency occurs in more systems, we study empirically the degree growth ﬂuctuations in two social networks. We ﬁnd both their ﬂuctuation exponents decrease logarithmically with the observation interval, presenting clear interval dependency that diﬀers from those observed in Internet in the speciﬁc manner but is still consistent in the tendency. By applying a progressive shuﬄing procedure, we ﬁnd an asynchronous response of the ﬂuctuation exponent and deduce the decline of the exponent might be related to the development of the internal correlation. These results indicate the general existence of the interval dependency in the degree growth ﬂuctuation and suggest its close connection with the correlation evolution, which could provide new insight to the related dynamics in complex networks.